THE POLITICAL ECONOMY OF LITHUANIA’S MEMBERSHIP IN THE EUROPEAN UNION: EXPECTATIONS AND THE EXPERIENCE OF FIVEY EARS - Vilpišauskas, Ramūnas (Politologija, 2015)
The article dicusses the impact of European Union membership on the economy, politics and policies of the new members states, in particular, Lithuania. It first presents the forecasts and arguments regarding the impact of EU enlargement that were dicussed before the enlargement in 2004/2007. It draws on the work of European integration literature stating that it was the approaching EU enlargement into the Central and Eastern Europe which caused the wave on theorizing the issue of enlargement which have been absent before. The main issue was to explain the reasons behind the EU decision to enlarge as well as the conditions for the effective application of EU norms into the acceeding countries. Most economic studies predicted that enlargement will contribute to the economic growth of acceeding countries (although the transfer of regulatory norms in some cases could be considered to be suboptimal), and the EU as a whole. There have been more uncertainty regarding the impact of the enlargement on the functioning of the EU and the compliance of the new members with the EU norms. The second section evaluates the experience so far, by discussing the studies which have been made on the impact of EU and concludes that, the enlargement has been a positive sum game for the economies of new member states (as well the EU), increasing trade and investments flows and contributing to the catching up with the rest of the EU. Lithuania and other new member states have been among the fastest growing economies in Europe for the last decade. However, it argues that the impact of the EU membership is mediated by domestic policies of each member state, and that Lithuania has not attampted to strengthen the positive impulses coming from the EU accession, in particular by postponing the structural reforms in the country. The return of the primacy of the domestic agenda after the EU accession have not resulted in the completion of the reforms, and might be one of the reasons for the radical economic decline of 2009 and forecasted slow recovery. What regards the impact of enlargement on the quality of institutions, so far most evidence shows that new members have not changed radically the functioning of the EU, and the implementation of the EU norms has been better than expected, with Lithuania consistently being one of the leading countries in terms of transposition of the internal market norms. This has been explained by the pre-accession habits of compliance as well as the institutional set up of European policy coordination in the accession countries. Comparatively good record of compliance also allows to maintain that EU is able to cope with the future enlargements as well. Finally, the article assesses the main European policy priorities in Lithuania, in particular the reasons for some failures (such as the failure to join the eurozone in 2007) and achievements (accession into Schengen area, acknowledgement of the importance of integrating the Baltic states into the energy market of the EU). It used the criteria of member state influance in the EU suggested by Helen Wallace to evaluate the record of Lithuania in advancing towards the implementation of two goals on the incomplete agenda of accession process (EMU and Schengen area membership) as well as the Eastern Neighborhood and Common Energy policies. It argues that most European policy failures have been due to the inconsistency and low credibility of some domestic policies. The article concludes by providing venues for future research of European policy after the enlargement, in particular the areas of in the impact of enlargement on the functioning of the EU, the participation of the new member states in the policy process of the EU as well as the ability to upload their domestic preferences on the EU agenda.